2013
DOI: 10.1371/journal.pone.0057284
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptors-1 and -3 Play Distinct Roles in the Regulation of Bladder Cancer Growth and Metastasis: Implications for Therapeutic Targeting

Abstract: Fibroblast growth factor receptors (FGFRs) are activated by mutation and overexpressed in bladder cancers (BCs), and FGFR inhibitors are currently being evaluated in clinical trials in BC patients. However, BC cells display marked heterogeneity in their responses to FGFR inhibitors, and the biological mechanisms underlying this heterogeneity are not well defined. Here we used a novel inhibitor of FGFRs 1–3 and RNAi to determine the effects of inhibiting FGFR1 or FGFR3 in a panel of human BC cell lines. We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 28 publications
(61 reference statements)
5
70
3
Order By: Relevance
“…Other studies have identified distinct genomic signatures associated with cancer progression, metastasis and response to therapeutic manipulations (Takata et al, 2005, Puzio-Kuter et al, 2009, Cheng et al, 2013, Van Allen et al, 2014, Groenendijk et al, 2016, Dyrskjot et al, 2003). Several groups used whole genome expression profiling to classify bladder cancer into various distinct subtypes (Cancer Genome Atlas Research N, 2014, Damrauer et al, 2014, Choi et al, 2014a, Lindgren et al, 2010, Sjodahl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified distinct genomic signatures associated with cancer progression, metastasis and response to therapeutic manipulations (Takata et al, 2005, Puzio-Kuter et al, 2009, Cheng et al, 2013, Van Allen et al, 2014, Groenendijk et al, 2016, Dyrskjot et al, 2003). Several groups used whole genome expression profiling to classify bladder cancer into various distinct subtypes (Cancer Genome Atlas Research N, 2014, Damrauer et al, 2014, Choi et al, 2014a, Lindgren et al, 2010, Sjodahl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In all lines, whether expressing wild-type or mutant FGFR3, we observed significantly reduced NFκB activation following knockdown of TAK1 (Figures 4 B, C). Addition of ligand enhanced this effect in MGHU3 cells, likely by activating other FGF receptors [42]. As a final test of NFκB activation, nuclear localization of the active p65 subunit of NFκB was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, they found no relationship between FGFR1 expression level and stage or grade (Tomlinson et al, 2009). Cheng et al (2013) demonstrated that FGFR1 has an important role in regulating proliferation and invasion/metastasis in "mesenchymal" and "epithelial" cells of human cancer bladder cells. By the contrary, Fischbach et al (2015) reported that amplifications of FGFR1 were found in only 1.6% of bladder cancer patients and FGFR amplifications are rare events in bladder cancer.…”
Section: Discussionmentioning
confidence: 95%